2023
DOI: 10.3390/healthcare11020275
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Spontaneous Bacterial Peritonitis (SBP) in Hepatitis B (HBV), and Hepatitis C (HCV) Liver Cirrhosis: A Systematic Review and Meta-Analysis

Abstract: Background and Aim: Spontaneous bacterial peritonitis (SBP) is a common infection in liver cirrhosis. This systematic review and meta-analysis provide detailed information on the prevalence of SBP among hepatitis B virus (HBV) and hepatitis C virus (HCV)-related liver cirrhosis globally. Methods: A systematic search for articles describing the prevalence of SBP in HBV and HCV-related cirrhosis was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines. Ou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
1
2
0
1
Order By: Relevance
“…The likely cause of this is unknown, but it can be attributed to the growing interest in the HBV cohort, the high index of HBV mutations, and the likelihood that HBV will advance to liver cancer and cirrhosis. The latter is consistent with other people's reports [19,47,[83][84][85]. Each study design makes a significant contribu-tion to the overall prevalence while also providing unique viewpoints on the connection between HBV and HCC in the Southeast Asian context [86,87].…”
Section: Discussionsupporting
confidence: 87%
“…The likely cause of this is unknown, but it can be attributed to the growing interest in the HBV cohort, the high index of HBV mutations, and the likelihood that HBV will advance to liver cancer and cirrhosis. The latter is consistent with other people's reports [19,47,[83][84][85]. Each study design makes a significant contribu-tion to the overall prevalence while also providing unique viewpoints on the connection between HBV and HCC in the Southeast Asian context [86,87].…”
Section: Discussionsupporting
confidence: 87%
“…This finding collaborates with an earlier report by Peter and Sofie (2005), who reported that genotype B+C is predominant in Asia [ 217 ]. The presence of viral hepatitis cirrhosis in Asian patients increases the propensity and generation of HBV recombinant [ 218 ]. Since several cases of recombinant genotypes have been reported across 27 Asian countries in this study ( Supplementary File S2 ), for optimal treatment outcomes, such infected patients will likely require more than the normal combinations of current HBV medications.…”
Section: Discussionmentioning
confidence: 99%
“…11 Our study revealed a high prevalence of Hepatitis C as an underlying etiology for chronic liver disease in SBP patients, which aligns with the global burden of Hepatitis C, particularly in regions like Asia. However, it's worth noting that a substantial proportion of patients had hepatocellular carcinoma, highlighting the frequent co-occurrence of these conditions and the increased risk they pose to patient mortality [16][17] .…”
Section: Discussionmentioning
confidence: 99%